A7.10 A combination of cellular biomarkers predicts clinical response to rituximab in rheumatoid arthritis. (13th February 2015) - Stradner, MH; Fessler, J; Dejaco, C; Brickmann, K; Graninger, WB; Brezinschek, HP
Abstract : Background and objectives: Although B cell depletion with rituximab (RTX) is an effective treatment strategy in rheumatoid arthritis (RA) one third of patients does not achieve low disease activity after rituximab. We have previously reported that the frequency of circulating plasmablasts is a negative predictor of RTX response; however, additional biomarkers could be helpful to better tailor treatment strategies to RA patients. In the present study we investigated, whether other lymphocyte subsets or combinations thereof are useful predictors of a clinical response to RTX treatment. Material and methods: RA patients receiving RTX for the first time were included in the Austrian rituximab registry. Clinical assessments, complete blood count and flow cytometry of lymphocyte subsets were obtained at baseline as well as at weeks 2 and 24 after RTX. Complete data was available for 48 patients. Logistic regression and receiving operating characteristic curve analyses were computed to analyse the predictive value of lymphocyte subsets for EULAR response and DAS ≤3.2 at week 24. Results: Seventy-five percent of patients had a moderate or good EULAR response at week 24. Responders had lower total lymphocyte counts (TLC), T cells and CD4 + T cells at baseline. Both, baseline TLC and baseline CD4 + T cell independently predicted EULAR response. Furthermore, a combination of TLC and plasmablast frequency independently predicted achievement of low disease activity. Less than 7% of patients with high TLC or plasmablast frequency reached low disease activity. Conclusions: In RA, patients with increased TLC or high plasmablast frequency are at high risk of failing therapy with RTX.